CELLULOSE SEPARATION PROCESS BASED ON LOCAL RAW MATERIALS – A STUDY OF THE INFLUENCE OF VARIOUS PARAMETERS - Ismatov Xayrulla Dilmuratovich; Asadova Ra’no Dilmuratovna; Khikmatova Dildora Khumaydullaevna; To’rayeva Nodira Turabjanovna (Web of Journals Publishing, 2025)
This article is about the issue of developing the linguistic competence of primary school students in terms of adjective vocabulary in their native language classes, as well as the methods used to form linguistic competence in the adjective vocabulary of primary school students. provides theoretical information and analyzes these methods.
Keywords: Competence, linguistic competence, linguistic analysis, phonetics, quality, grammatical analysis.